Biohack your brain : how to boost cognitive health, performance & power - Willeumier, Kristen; Toland, Sarah (William Morrow, an imprint of HarperCollins Publishers, 2020)
A neuroscientist's groundbreaking, science-driven plan for revitalizing, nourishing and rejuvenating your most essential asset--your brain.Your brain is the most essential organ in your body. The brain and spinal cord are intimately connected to every bodily system and organ, so when it is balanced everything in your body and mind will function more efficiently. It's vitally important to take proactive steps now, or you risk losing everything, including your ability to think clearly, be creative, remember details, solve problems and retain your memory.In Biohack Your Brain, leading neuroscientist Dr. Kristen Willeumier reveals how you can change your brain by making simple and easy modifications to your lifestyle. Combining clinical experience with revolutionary science, she details how biohacking your brain can boost your cognitive performance and so much more.Dr. Willeumier's essential guidebook shows you the most effective techniques to prevent memory loss and neurodegenerative disorders like Alzheimer's disease--and even how to overcome negative thoughts and stress. Through research and case studies, you'll learn how to upgrade your nutritional choices along with the effective use of supplements, brain games, and physical activity to overcome cognitive damage, whether it's from previous injuries, such as a concussion or a bad fall or from the effects of living in modern day times.Dr. Willeumier shares her own story alongside those from the NFL players and other clients she has worked with to help you leverage the latest research to find personal solutions. Biohack Your Brain teaches you how to take better care of your brain, and also how to release excess weight, enhance your memory, increase your energy and vitality in order to create the best health and life possible.